Grounds of the State Restructuring Nepal - Ghimire, Tara Nath (Patan Prospective Journal, 2022)
Unitary and federal systems are in use in the state-building process. Nepal has a long history of unitary rule and is in the process of institutionalizing the federal system. It is a form of governing structure. The unitary system and the federal system are the prevailing governing systems. Looking at the governing history, the unitary and the federal government can be found on normal. Both systems have their characteristics and process of formation. Some countries have transformed from a unitary system to a federal one, while others have adopted a unitary system after the collapse of federalism. Various reasons and causes have been guiding the form of federalism. This article provides a brief overview of the external and internal reasons for the demand for the federal system to restructure Nepal. The study has attempted to analyze the question that the external and internal reasons for the implementation of the federal system through the restructuring process of the unitary system in Nepal. The study is based on secondary data only to reach conclusions.